Electro‐mediated PhotoRedox Catalysis for Selective C(sp3)–O Cleavages of Phosphinated Alcohols to Carbanions. (16th August 2021) - Tian, Xianhai; Karl, Tobias A.; Reiter, Sebastian; Yakubov, Shahboz; de Vivie‐Riedle, Regina; König, Burkhard; Barham, Joshua P.
Abstract: We report a novel example of electro‐mediated photoredox catalysis (e‐PRC) in the reductive cleavage of C(sp 3 )−O bonds of phosphinated alcohols to alkyl carbanions. As well as deoxygenations, olefinations are reported which are E ‐selective and can be made Z ‐selective in a tandem reduction/photosensitization process where both steps are photoelectrochemically promoted. Spectroscopy, computation, and catalyst structural variations reveal that our new naphthalene monoimide‐type catalyst allows for an intimate dispersive precomplexation of its radical anion form with the phosphinate substrate, facilitating a reactivity‐determining C(sp 3 )−O cleavage. Surprisingly and in contrast to previously reported photoexcited radical anion chemistries, our conditions tolerate aryl chlorides/bromides and do not give rise to Birch‐type reductions. Abstract : Beyond C(sp 2 )–X cleavage: We report reductive cleavages of C(sp 3 )−O bonds of phosphinated alcohols to alkyl carbanions by electro‐mediated photoredox catalysis. Deoxygenations as well as E ‐ or Z ‐selective olefinations are reported. Surprisingly, reactions tolerate C(sp 2 )‐X cleavages such as aryl halides. Radical ion catalyst‐substrate preassembly is key in enabling reactivity and overturning conventional redox chemoselectivity.